Long-term effects of oppositional child treatment with mothers as therapists and therapist trainers. - Strain, P S (1982)
The follow-up data reported represent a long-term (3 to 9 years out of treatment) evaluation of 40 children who were clients of the Regional Intervention Program (RIP) from 1969 to 1978. As 3-, 4-, and 5-year olds, these youngsters exhibited severe and prolonged tantrums, continual opposition to adults' requests and commands, and physical aggression toward parents. Each child and mother participated in a standardized intervention package modeled after Wahler's Opposition Child Treatment. Results from school and home-based follow-up showed that: (a) commands, demands, or requests made by parents were likely to be followed by former clients' compliance; (b) former clients' social interactions in the homes were overwhelmingly positive and their nonsocial behavior was by and large appropriate; (c) parent behavior in the home was consistent with the child management skills taught many years ago; (d) there were no differences between the compliant, on-task, social interaction and appropriate/inappropriate nonsocial behaviors of former clients and randomly selected class peers; (e) there were no differences in teachers' commands, negative feedback, positive social reinforcement, and repeated commands that were directed toward either former clients or randomly selected class peers; (f) both teachers' and parents' rating of former clients on the modified Walker Problem Behavior Checklist were highly correlated; (g) there were no differences in teachers' rating of former clients and class peers; and (h) of all the studied demographic variables, only age that treatment began and family intactness were related to current levels of behavior.